Pengaruh Attitude, Sertifikasi Halal, Promosi dan Brand terhadap Purchase Intention di Restoran Bersertifikasi Halal - Diah Ayu Legowati; Farah Nisa Ul Albab (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2019)
Research related to the purchase intention of halal products has been the concern of many researchers in recent years. This study aimed to determine the relationships between attitude, halal certification, promotion, and brand related to the intention of purchasing at the halal-certified restaurant. The data were collected through a self-administered questionnaire survey consisting of 132 consumers. We found that the attitude, halal certification, and brand were significantly influential towards the purchase intention at the halal-certified restaurant, whereas a promotion was not significantly influential